Cinematic identity : anatomy of a problem film - Patton, Cindy, 1956- (Theory out of bounds, 2007)
Cindy Patton takes Pinky as a starting point to meditate on the critical reception of this and other Òproblem filmsÓ and to explore the larger issues they raise about race, gender, and sexuality. Patton historicizes Òproblem filmsÓ and the arrival of Method acting in Hollywood, and in doing so offers new perspectives on identity politics, from feminism to the gay rights movement.